SISTEM INFORMASI PENGELOLAAN BISNIS PADA KANTIN PT. SAT NUSAPERSADA BATAM: BUSINESS MANAGEMENT INFORMATION SYSTEM AT THE CANTINE OF PT. SAT NUSAERSADA BATAM - Okta Veza; Hanafi; Nurul Maghfiroh (Engineering and Technology International Journal, 2020)
Sat Nusapersada is one of the companies in the city of Batam. The company has six canteens as food providers to support and meet the needs of its employees. These six canteens still use the conventional process, where employees have to come directly to order food. Long queues cause canteen managers to make mistakes in the food ordering process. This is a problem for the canteen manager. With the availability of information and communication technology, it can be used to develop a canteen business management business. So we need a system that can order food online so that it can make it easier for customers to order food at the canteen of PT. Sat Nusapersada. From the business management information system at the canteen of PT. Sat Nusapersada website-based using the SDLC waterfall method which aims to assist employees in ordering food is one of the goals in making this system. So that this system is expected to make it easier for customers to place orders, and can improve canteen management services for customers who will place orders. This information system uses PHP and CSS as source code and MySQL as database connection.